Note sul Diario di viaggio sulle Alpi Bernesi di Hegel (Materiali di Estetica. Terza serie, 2021)
Hegel’s Travel Diary in the Bernese Alps, a real daily diary, dating back to the summer of 1796, is rather neglected by Hegelian critics, but is full of interesting implications, whether naturalistic or philosophical. In fact, various levels of interpretation are intertwined, from anthropological to geographical, aesthetic and widely cultural level. There we find not only and not so much the confirmation of Hegel's lack of love for the mountains, but above all his subtle aptitude for grasping its poetic and spiritual inspiration. It is no coincidence that the Eleusis poem that Hegel sent to Hölderlin in August 1796 is called into question here.
Keywords: Bernese Alps; Hegel; Eleusis